Wildlife trade dynamics: exploring bushmeat market with a view toward social and ecological justice in Ibadan Metropolis Nigeria - Olunusi, Bright O. (Frontiers in Conservation Science, 2024)
This study examines the bushmeat trade in Ibadan Metropolis, Nigeria, through the lens of environmental justice, focusing on sustainable livelihoods and wildlife conservation. Environmental justice in this context seeks to ensure fair economic opportunities for bushmeat marketers, predominantly women (93%), while protecting vulnerable wildlife species. The surveyed marketers—90% of whom were married—face social inequalities, with only 50% having secondary education and 10% lacking formal education. Most marketers sell bushmeat to household consumers and travelers, raising concerns about the potential spillover of wildlife products beyond Nigeria’s borders, with implications for conservation and zoonotic disease risks. ANOVA results show that greater experience leads to higher profits from species like grasscutter (Thryonomys swinderianus; P = 0.005) and nile monitor lizard (Varanus niloticus; P = 0.001). As key species such as West African crocodile (Crocdylus suchus), African leopard (Panthera pardus), and ground pangolin (Manis temminckii) decline in availability in traditional hunting grounds, this study emphasizes the urgent need for conservation policies that promote sustainable trade practices and provide alternative livelihoods. These strategies would advance the science of environmental justice by reducing pressure on wildlife (ecological justice) while ensuring stable incomes for marketers (social justice).